Traditional institution for enhancing the sustainability of irrigation management in West Sumatra Indonesia - Ifdal, Ifdal; Utami, Ami Sukma (International Journal of Agricultural Sciences, 2023)
Indigenous institutions that have been existing within the community for hundreds of years ago can contribute to effective natural resources management, especially by encouraging farmers' participation in irrigation activities. However, due to a new institution introduced by the Indonesian government, such as the water users' Associations ("P3A" in Bahasa), institutional problems, such as low participation from farmers in irrigation activities, have occurred in some regions where the traditional institution has been disappearing from irrigation management. Nevertheless, some communities appropriately manage the irrigation system by integrating traditional institutions into the current irrigation system. This study aims to re-assess the importance of the traditional institution in managing irrigation systems in West Sumatra. The qualitative method was used to collect data in Agam district from January 2022 to August 2022. Two P3As (P3A Karya Mandiri dan P3A Jorong Biaro) were selected to evaluate the traditional institution in irrigation management. This study found that matrilineal land ownership (ulayat kaum in Minangkabau language) can ensure irrigation water supply for each system and the continuity of rice farming. Furthermore, mufakat (deliberation to reach consensus) in determining irrigation management can encourage farmers' participation in irrigation activities and avoid conflict over water, especially during the dry condition. To re-implement indigenous institution in irrigation management, collaborative action must be performed to create mutual understanding regarding indigenous institutions between farmers and policy makers.